Characterizaion of the mechanism underlying auxin-induced seed arrest in Arabidopsis thaliana - Venkatesan, Sowmiya Devi (SLU/Dept. Of Plant Biology, 2020)
In flowering plants, seeds are produced as a result of double fertilization, whereby the haploid egg cell and the diploid central cell fuse with one of the two haploid sperm cells giving rise to a diploid embryo and a triploid endosperm, respectively. The endosperm serves as the major nutrient source for the developing embryo yet the molecular mechanisms pertaining to its development are not fully understood. Interploidy hybridizations cause improper endosperm development, establishing a reproductive barrier called the triploid block. Recent studies have linked the phytohormone auxin to the above process. Here, we show that an increase in auxin biosynthesis in the endosperm induced a seed abortion phenotype that resembles the phenotype of paternal-excess triploid seeds. Among the similarities, nrpd1, a mutant in RNA POLYMERASE IV, could impair the seed abortion phenotype induced by both triploid block and auxin over-expression, suggesting a vital role for the RNA silencing pathways in mediating the auxin and paternal genome dosage response. To test this link between RNA silencing and auxin-induced seed abortion, several loss-of-function mutants of the RNA silencing pathway have been assayed for their ability to affect the seed abortion phenotype induced by auxin overexpression. We found dcl3, a member of the RNA-directed DNA methylation (RdDM) pathway to have the same effect as nrpd1. Therefore, we propose that at least a part of the RdDM pathway is involved in the seed abortion phenotype induced by the auxin overexpression.